Entrepreneurship Development Based on Teaching Factory in Fashion Design Skill Program at Vocational High School - Iliani, Ana Isro; Nurhadi, Didik; Zahro, Siti; Ching, Su Jo (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
Vocational education development must be based on the required skills from the workplace to create creative and skilled laborers with Indonesian government programmed a BMW (Bekerja, Melanjutkan studi, dan Wirausaha, or working, further studying, and being entrepreneurs) program for this matter. This study aimed to explore entrepreneurship learning based on teaching factory for students with fashion design skills in vocational high schools. This research used a descriptive method and qualitative approach. The data was analyzed using the interactive model and was validated using triangulation and member checking. The finding showed that entrepreneurship learning based on teaching factory in vocational high schools was conducted through the development stage, implementation, and evaluation. The effect was a 20 percent increase in graduates' absorption in industries and entrepreneurship. Thus, it can be concluded that entrepreneurship learning based on teaching factory in vocational high schools significantly influenced graduates to work